2008
DOI: 10.4049/jimmunol.180.5.3543
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell-Fibroblast Interactions Induce Matrix Metalloproteinase-9 Release from Fibroblasts: Role for IgE-Mediated Mast Cell Activation

Abstract: Mast cells adhere to fibroblasts, but the biological effects of adhesion are not well understood. We hypothesized that these adhesive interactions are important for tissue remodeling through the release of matrix metalloproteinases (MMP). Murine bone marrow cultured mast cells (BMCMC) were cocultured with NIH-3T3 fibroblasts or murine lung fibroblasts (CCL-206) and supernatants analyzed for MMP-9 release by gelatin zymography. Coculture of BMCMC for 24 h with NIH-3T3 or CCL-206 fibroblasts increased the releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 50 publications
2
23
0
1
Order By: Relevance
“…The increase in MMP14, however, was only partially suppressed (by 45%) with apocynin. These TNF-mediated changes in MMP expressions were 1 The online version of this article contains supplemental material. well reflected in the proteolytic activities of these culture systems.…”
Section: Tnf-induced Superoxide Production Is Accelerated and Strongementioning
confidence: 97%
See 1 more Smart Citation
“…The increase in MMP14, however, was only partially suppressed (by 45%) with apocynin. These TNF-mediated changes in MMP expressions were 1 The online version of this article contains supplemental material. well reflected in the proteolytic activities of these culture systems.…”
Section: Tnf-induced Superoxide Production Is Accelerated and Strongementioning
confidence: 97%
“…S1A). 1 Concomitantly, a rise in nitrate/nitrite (NO 2 /NO 3 ) levels was also detected as measured by Griess reaction assay (Fig. 2B), suggestive of enhanced activity of NOS and elevated NO production.…”
Section: Tnf-induced Superoxide Production Is Accelerated and Strongementioning
confidence: 98%
“…Mouse bone marrow-derived mast cells (BMMCs) were generated from 6-week-old C57BL/6 mice according to the method described previously [15]. Briefly, bone marrow cells in alpha modification of Eagle's medium (α-MEM; Invitrogen, Carlsbad, Calif., USA) containing 10% FBS, 100 U/ml penicillin G, 100 μg/ml streptomycin, 1 m M sodium pyruvate, 0.1 m M nonessential amino acid, and 50 μ M 2-mercaptoethanol (Invitrogen) supplemented with 10 ng/ml mIL-3 (PeproTech, Rocky Hill, N.J., USA) were cultured at 37°C in a humidified atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In this study, mast cells were found in close contact with fibroblasts. Mast cell activation is a characteristic feature of chronic inflammation, a condition that may lead to fibrosis as a result of increased collagen synthesis by a fibroblast [140][141][142][143][144].…”
Section: Cell-cell Interaction In Dermal Resident Cellsmentioning
confidence: 99%
“…Fibroblasts can modulate the functions of both mast cells and eosinophils, which also increase the amount of melanocytes and melanin pigment [141][142][143].…”
Section: Cell-cell Interaction In Dermal Resident Cellsmentioning
confidence: 99%